Pengaruh Financial Sustainability Terhadap Jangkauan BPR Syariah Di Propinsi Sumatera Barat - Hidayatul Arief; Iiz Izmuddin; Hesi Eka Puteri (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2019)
This study aims to analyze the effect of Financial Sustainability as proxied by CAR, FDR, ROA, ROE, NOM and BOPO on the outreach of BPR Syariah that are proxied by the number of financing customers in West Sumatra Province. The study population was all BPR Syariah in the Province of West Sumatra, the research sample was taken using purposive sampling technique to obtain a sample of 6 companies. The data analysis technique used is the panel data regression method which is a combination of cross section data and time series data using STATA 13 software. While testing the hypothesis using the GLS model with a significance level of 5%. The results of the analysis showed that partially the FDR and ROA variables had a significant effect on increasing outreach while the other variables had no significant effect on the outreach of BPR Syariah in West Sumatra Province. Financial Sustainability has a significant simultaneous effect on the outreach of Sharia Rural Banks in West Sumatra Province. Penelitian ini bertujuan untuk menganalisis pengaruh Financial Sustainability yang diproksikan oleh CAR, FDR, ROA, ROE, NOM dan BOPO terhadap jangkauan BPR Syariah yang diproksikan dengan jumlah nasabah pembiayaan di Propinsi Sumatera Barat. Populasi penelitian adalah seluruh BPR Syariah yang ada di Propinsi Sumatera Barat, sampel penelitian diambil menggunakan teknik purposive sampling sehingga diperoleh sampel sebanyak 6 perusahaan. Teknik analisis data yang digunakan adalah metode regresi data panel yang merupakan gabungan dari data cross section dan data time series dengan menggunakan perangkat lunak STATA 13. Sedangkan pengujian hipotesis menggunakan model GLS dengan tingkat signifikansi 5%. Hasil analisis menunjukkan secara parsial variable FDR dan ROA memilik ipengaruh signifikan terhadap peningkatan jangkauan sedangkan variable lainnya berpengaruh tidak signifikan terhadap jangkauan BPR Syariah di Propinsi Sumatera Barat. Financial Sustainability memiliki pengaruh yang signifikan secara simultan terhadap jangkauan BPR Syariah di Propinsi Sumatera Barat